Absolute quantitative Lipidomics reveals lipid differences in milk fat globules of yak and German Simmental cattle - Yili Liu; Peng Wang; Kai Wang; Yueyue Li; Zifeng Ma; Jian Li; Daoliang Lan; Liqiang Han; Wei Fu (Food Chemistry: X, 2025)
Lipids in milk fat globules (MFGs) are critical for nutrition and health, and yak milk, rich in milk fat, is vital for herders. This study used absolute quantitative lipidomics to compare the differences in MFG lipids in mature milk between yak (Y) and German Simmental cattle (GS). Compared with GS, Y showed higher milk fat (5.37 ± 1.70 vs. 2.31 ± 1.27 %), larger MFG size (D[4,3]: 8.69 vs. 4.31 μm). 2414 lipid species from 43 lipid subclasses in Y and GS were identified, and 187 significantly different lipids (SDLs; variable importance for the projection (VIP) > 1, fold change (FC) > 1.5 or < 0.67 with P < 0.05) were then screened out. TG(18:0_18:1_20:1), TG(18:1_18:3_18:3), Hex1Cer(d14:2_16:0), and TG(4:0_16:0_23:0) were potential lipid biomarkers. These SDLs involved 23 KEGG metabolic pathways, with sphingolipid metabolism being the most relevant. Our findings enhance understanding of MFG lipid differences between Y and GS, promote the development of functional yak milk product, and lay a quality identification foundation.